The influence of the Cavitation and Flashing phenomena in the formation of “scallops” within karstic caves. The Chorros Cave case (Albacete, Spain): The theory of the inverse siphon in the “Reventón” phenomenon - F. Pavía Alemany; T. Rodríguez-Estrella (Ingeniería del Agua)
The influence of the negative pressures of Cavitation and Flashing phenomena in the formation of “scallops”, within karstic caves, is hereby studied. In this sense, the particular case of the Chorros Cave (Albacete, Spain) is analyzed, and the theory of the inverse siphon is proposed in order to explain the “Reventón” phenomenon.